Modal Ventura Syariah dalam Tinjauan Hukum Islam - Zimq Marquiza; Liza Septiyani; Muhammad Faqih Fahriza; Dina Aslamiya Anjalina; Muhammad Taufiq Abadi (CV. ALIM'SPUBLISHING, 2024)
The presence of sharia venture capital is needed to provide access to capital for sharia startups. Sharia venture capital not only provides capital but also supports and guides sharia startups so they can grow and develop. Even though venture capital companies in a region have not yet been named sharia venture capital, but they have implemented sharia principles, because in financing. This research is a type of research using qualitative methods. The information and data collection technique in this research is carried out through library research (library study), using library sources that are related to the research subject that has been formulated. The purpose of this research is to find out about sharia venture capital, the history of sharia venture capital and the business activities of legal entities or laws regarding sharia venture capital.